Laterality Does Not Affect the Depth Perception, but Interpupillary Distance - Murat Aslankurt; Lokman Aslan; Adnan Aksoy; Murat Özdemir; Şenol Dane (Journal of Ophthalmology)
In this study, which investigates the relationship between the levels of stereopsis with eye and hand dominance or interpupillary distance, 120 healthy young volunteers were investigated. Eye dominance was determined by modified Miles technique following a complete eye examination. Handedness was assessed with the Edinburgh handedness inventory. Interpupillary distance was measured with millimetric ruler. Stereoacuity was measured in both contour (Titmus test) and random dot (TNO test) stereograms. The stereopsis scores were evaluated in terms of hand or eye dominance. The correlation between stereopsis score and interpupillary distance was assessed. Main outcome measures were stereopsis scores according to hand and eye dominance. As a result, right- and left-handed individuals showed no differences in terms of stereopsis. No differences were found in stereopsis scores between right- and left-eye dominant people. There was a correlation between interpupillary distance and the depth of stereopsis (r=-0.248,P<0.05). Contrary to the expectation, the left and right dominant individuals did not differ in levels of stereopsis. Interpupillary distance has a positive effect on stereopsis.